PENGUATAN MODERASI BERAGAMA DI LINGKUNGAN PONDOK PESANTREN - Kurniawan, Risky; Rindiyani, Rindiyani; Supriyati, Supriyati (STAI Darul Qalam Tangerang, 2023)
The purpose of this article is to provide an understanding of the importance of moderate attitudes in maintaining religious diversity in Indonesia and to explain the important role of Islamic boarding schools in strengthening religious moderation. Islamic boarding schools play an important role in strengthening religious moderation by maintaining the diversity of their students, providing moderate and balanced religious education, teaching tolerance values, and organizing activities that strengthen tolerance and harmony among people of different religions. By doing so, it is expected that Islamic boarding schools can become a safe and comfortable place for students from various religious backgrounds, and can contribute to strengthening religious moderation in society as a whole